Towards a High-Power Si@graphite Anode for Lithium Ion Batteries through a Wet Ball Milling Process - Marta Cabello (Molecules, 2020)
Silicon-based anodes are extensively studied as an alternative to graphite for lithium ion batteries. However, silicon particles suffer larges changes in their volume (about 280%) during cycling, which lead to particles cracking and breakage of the solid electrolyte interphase. This process induces continuous irreversible electrolyte decomposition that strongly reduces the battery life. In this research work, different silicon@graphite anodes have been prepared through a facile and scalable ball milling synthesis and have been tested in lithium batteries. The morphology and structure of the different samples have been studied using X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, and scanning and transmission electron microscopy. We show how the incorporation of an organic solvent in the synthesis procedure prevents particles agglomeration and leads to a suitable distribution of particles and intimate contact between them. Moreover, the importance of the microstructure of the obtained silicon@graphite electrodes is pointed out. The silicon@graphite anode resulted from the wet ball milling route, which presents capacity values of 850 mA h/g and excellent capacity retention at high current density (≈800 mA h/g at 5 A/g).